Pengaruh Human Resource Information System (HRIS) terhadap Efisiensi Kerja Karyawan di Era Industry 4.0: A Literature Review - Septiani Damaiyanti; Syahrial Shaddiq; Khuzaini; Zakky Zamrudi (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to comprehensively examine the effect of Human Resource Information System (HRIS) on employee work efficiency in the Industry 4.0 era using a literature review approach. The rapid development of information technology encourages organizations to adopt digital systems in human resource management to improve operational effectiveness and efficiency. The research method employed is a literature study by analyzing relevant scientific articles published between 2015 and 2025 from various academic databases. The analysis technique involves identification, selection, evaluation, and synthesis of the literature.The findings indicate that HRIS has a positive impact on employee work efficiency through the automation of administrative processes, improved data accuracy, and real-time access to information. HRIS implementation also enhances employee productivity and supports more effective decision-making. However, its effectiveness depends on employees’ digital competencies, system quality, and organizational support. This study provides theoretical contributions to the development of technology-based human resource management and practical implications for organizations in optimizing HRIS to improve work efficiency in the Industry 4.0 era.